The Role of Sustainable Tourism Development on Tourist Satisfaction among Local Tourist in Malaysia - Afeira Helena Binti Zainudin (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
Tourism business has become a thriving and competitive industry recently. This industry is becoming increasingly vital to strengthen the country's economy as well as increase popularity and awareness through publicity. In today's world, travelling is the ideal kind of pleasure for people of all ages. People will travel to destinations that offer tourist facilities and experiences. It should be noted that the impact of sustainable tourism on tourist satisfaction is a critical research topic in the tourism sector. Despite a substantial amount of study on satisfaction, it remains unclear whether sustainable tourism influences on tourist satisfaction. Therefore, this assessed the visitor’s behaviour literature gap by focusing on the relationship between sustainable tourism on satisfaction from the customer’s perspective. The survey was distributed to the local tourist. A total of 202 respondents from Seremban, Malaysia was involved. This study identifies that economic benefit, sustainable tourism and perceived experience user generated content positively influence tourist satisfaction. Analysis from the study shows that the tourist satisfaction and recommend Negeri Sembilan as a holiday destination.